Approval procedure for active substances in plant protection products - doubts of scientific certainty as a source of controversy. Analysis of systemic imperfections on the example of glyphosate - Anna Gembicka; Jakub Ali Farhan (Eastern European Journal of Transnational Relations, 2023)
The purpose of this article is to examine the causes of recurring doubts regarding the safety of plant protection products used in the European Union. Plant protection products are a particular subject of regulation. All standards concerning them require prior in-depth scientific research in the field of exact sciences. Achieving adequate safety of humans, animals and the environment in connection to the use of plant protection products requires not only good law, but a law based on representative research and scientific certainty. Bearing in mind the above, the authors undertook an analysis of what seems to be the cause of significant social doubts as to the actual achievement of the purposes of Regulation 1107/2009, i.e. inclusion of scientific research in the procedure of approval of active substances in plant protection products. First, the approval procedure for the active substance of the plant protection product was presented, and then the main shortcoming of the procedure was analyzed on the example of the approval of glyphosate. In the authors' opinion, guidance documents on literature review should be revised to reflect the best scientific practice, and their standards should be enforced, in particular, to ensure that there is no doubt about the objectivity of the literature review.